Comprehensive circRNA Expression Profile and Construction of circRNAs-Related ceRNA Network in a Mouse Model of Autism - Wang, Ji; Yang, Zhongxiu; Chen, Canming; Xu, Yang; Wang, Hongguang; Liu, Bing; Zhang, Wei; Jiang, Yanan (Frontiers in Genetics, 2021)
Autism is a common disease, which seriously affect the quality of life. The role of circular RNAs (circRNAs) in autism remain largely unexplored. We aimed to detected the circRNA expression profile and constructed a circRNA-based competing endogenous RNA (ceRNA) network in autism. Valproate acid was used to establish an in vivo model of autism in mice. A total of 1059 differentially expressed circRNAs in autism group was identified by RNA sequencing. And 477 circRNAs were upregulated and 582 circRNAs were downregulated in autism group. The expression of novel_circ_015779 and novel_circ_035247 were detected by real-time PCR. A ceRNA network based on altered circRNAs was established, with 9715 nodes and 150408 edges. Module analysis was conducted, and pathway enrichment analysis was conducted. The top three modules were all correlated with autism-related pathways involving ‘TGF-beta signaling pathway’, ‘Notch signaling pathway’, ‘MAPK signaling pathway’, ‘long term depression’, ‘thyroid hormone signaling pathway’, etc. The present study reveals a novel circRNA involved mechanisms in the pathogenesis of autism.